Religious Orientation and the Influence of Nurture: The Examination of Environmental Influences in Critical Developmental Periods - Nolan Branson (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2016)
Social psychologists are increasingly interested in the growth of irreligion, defined by Lugo (2015) as identification with no particular religious affiliation. Findings that suggest that religion is a product of evolution (For review see Wilson, 2002; Richerson, & Christiansen, 2013; Purzycki, Haque, & Sosis, 2014) have influenced this social psychological research, warranting the question: If religious tendencies were strictly a product of evolution, then how does one explain the phenomenon of irreligion? Current research on the topic indicates that there might be an overlap between heredity traits that influence underlying evolutionary community tendencies and the heritable influences behind religiosity (Lewis, 2013). However, in another recent study, Brandon Burr and colleagues found that most test subjects believed that their personal religious beliefs developed as a result of childhood exposure to a particular religion (Burr, Kuns, Atkins, Bertram, & Sears, 2015). While Lewis’s research examined the potential genetic influence that might underpin religiosity, I, like Burr, take the environmental nurture approach and examine the correlation between attendance of religious services during development and religious affiliation as an adult. After analyzing data collected by the Pew Research Center’s Forum on Religion & Public Life for their study, Faith in Flux: Change in Religious Affiliation in the U.S. (Lugo, 2008), I find significant mean differences in attendance of religious services across three groups of individuals: those who identified as religious during childhood and are now atheist, those who identified as religious during childhood and are now agnostic, and finally those who identified as religious during childhood and are now unaffiliated with any particular religion. I find that members of all groups of rare to occasional attendance of religious services, during adolescent development, have converted from their former religion to one of the three irreligious categories.